2008
DOI: 10.1002/app.28979
|View full text |Cite
|
Sign up to set email alerts
|

Properties of soy protein isolate/poly(vinyl alcohol) blend “green” films: Compatibility, mechanical properties, and thermal stability

Abstract: Blend films from nature soy protein isolates (SPI) and synthetical poly(vinyl alcohol) (PVA) compatibilized by glycerol were successfully fabricated by a solution-casting method in this study. Properties of compatibility, mechanical properties, and thermal stability of SPI/PVA films were investigated based on the effect of the PVA concentration. XRD tests confirm that the SPI/ PVA films were partially crystalline materials with peaks of 2y ¼ 20. And, the addition of glycerol will insert the crystalline structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
40
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 38 publications
6
40
0
Order By: Relevance
“…The % crystallinity of the control film was higher than to the nanoparticle containing film which confirms that the addition of nano particle reduced the crystallinity of the film. Su et al (2008) observed the same finding while developing the soya protein based edible film. They reported that the polyvinyl alcohol and glycerol affected the crystalline structure of film as it may insert into crystalline structure of the film and can modify the microstructure of the film.…”
Section: X-ray Diffractionsupporting
confidence: 64%
“…The % crystallinity of the control film was higher than to the nanoparticle containing film which confirms that the addition of nano particle reduced the crystallinity of the film. Su et al (2008) observed the same finding while developing the soya protein based edible film. They reported that the polyvinyl alcohol and glycerol affected the crystalline structure of film as it may insert into crystalline structure of the film and can modify the microstructure of the film.…”
Section: X-ray Diffractionsupporting
confidence: 64%
“…Small features at 2380 and 2164 cm −1 (which assigned as C-O stretching mode) remained unchanged in all of models. The absorption bands at 1241-1472 cm −1 , which are attributable to the C-O-O and C-N stretching and N-H bending (amide III) vibrations of gluten and inulin (Su et al 2008), were possibly enhanced due to increase of model components. The bands at 1161, 1079 and 1022 cm −1 are due to the C-O stretching mode of the C-OH groups of gluten as well as the C-O groups of inulin (De Marchi et al 2009;Parker 1971;Shen et al 2010).…”
Section: Inulin -Gluten Interactionmentioning
confidence: 97%
“…2 shows the FTIR spectra for the films prepared with 10% acid or oil related to the control film. The main absorption peaks for the control film are related to C = O stretching at 1633 cm À1 (amide I), N-H bending at 1514 cm À1 (amide II), and C-N stretching (amide III) at 1232 cm À1 (Su et al, 2008). The broad band observed at 3271 cm À1 is attributable to free and bound O-H and N-H groups, which are able to form hydrogen bonding with the carbonyl group of the peptide linkage in the protein.…”
Section: Fourier-transform-infrared Spectroscopy (Ftir)mentioning
confidence: 99%